2008
DOI: 10.1073/pnas.0711651105
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging analysis of an anesthetic gas that blocks human emotional memory

Abstract: It is hypothesized that emotional arousal modulates long-term memory consolidation through the amygdala. Gaseous anesthetic agents are among the most potent drugs that cause temporary amnesia, yet the effects of inhalational anesthesia on human emotional memory processing remain unknown. To study this, two experiments were performed with the commonly used inhalational anesthetic sevoflurane. In experiment 1, volunteers responded to a series of emotional and neutral slides while under various subanesthetic dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 35 publications
3
70
2
Order By: Relevance
“…This 'emotional tag' will strengthen synapses that have just been activated in another brain-memory system that is engaged in the learning situation eventually leading to the reinforcement of consolidation of that event [47,48]. In support of this view, recent work has shown that suppression of the amygdala to hippocampal effective connectivity blocks the emotion-induced memory-enhancing effect [49].…”
Section: Memory Modulation By Emotionalitysupporting
confidence: 48%
“…This 'emotional tag' will strengthen synapses that have just been activated in another brain-memory system that is engaged in the learning situation eventually leading to the reinforcement of consolidation of that event [47,48]. In support of this view, recent work has shown that suppression of the amygdala to hippocampal effective connectivity blocks the emotion-induced memory-enhancing effect [49].…”
Section: Memory Modulation By Emotionalitysupporting
confidence: 48%
“…Higher-order association areas are more sensitive to hypnotic agents than lower-order processing regions [29,40,41]. At low concentrations, hypnotic agents reduce but do not abolish connectivity and anticorrelation of DMN and ECN [42 ,43 ,44 ], and of other higher-order networks including emotional and memory networks [45], while connectivity is preserved or even increased in lower-order sensory and motor networks [46]. An impairment of sub-cortical thalamoregulatory systems has also been reported at low concentrations that could account for an altered cortical integration of information [47 ], despite preserved activation of the thalamus by external stimuli.…”
Section: Recent Advances In the Understanding Of Anesthesia-induced Amentioning
confidence: 99%
“…56 Memory for emotional encounters was blocked by sub-anesthetic concentrations of sevoflurane (0.25%), desflurane (1.5-2 times MAC-awake), and propofol (1.5-2 times MAC-awake). 57,58 At MAC-equivalent concentrations, some anesthetics are more effective than others at preventing memory. For example, both isoflurane and nitrous oxide suppressed memory in a dose-dependent manner, although isoflurane was more effective than MAC-equivalent concentrations of nitrous oxide.…”
Section: Blockade Of Memory By General Anesthetics In Humans and Labomentioning
confidence: 99%